Pulmonary artery debanding in the cath lab: Lessons learned! - Zareef, Rana; Hassan, Sally Al; Younis, Nour; Tannoury, Theresia; Rassi, Issam El; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2022)
Background: Although primary definitive repair of congenital heart disease has become the preferred management approach, pulmonary artery banding remains a valuable palliative procedure used to restrict pulmonary blood flow in certain conditions. However, when the band is to be removed, another surgical intervention is usually required. Methods: To describe percutaneous removal of pulmonary artery band, the medical records of patients who underwent this procedure were reviewed. Results: Between 2000 and 2020, 143 patients underwent pulmonary artery banding. Of these, we attempted balloon debanding of the pulmonary artery in four patients. The average age of patients was 36 ± 6.24 months and weight 37.1 kg at the time of the procedure. Band removal via catheter was successful in three cases and was associated with an adequate reduction in pressure gradient across the pulmonary artery band site (average of 71.67 ± 12.58 to 23.67 ± 2.89 mm Hg). None of the patients experienced complications during or after the procedure. Follow up data after discharge (3-10 years) provides reassuring and satisfactory results. Conclusion: Based on our findings, we suggest that percutaneous removal of the pulmonary artery band might be a safe and effective alternative to surgical debanding. However, studies with larger population size are required for further clinical implementation of the technique.